The Application and Optimization Path of Supply Chain Finance in Financing for Small and Medium-Sized Enterprises - Teng Youming (SHS Web of Conferences)
With the acceleration of economic globalization and market competitiveness, small and mediumsized businesses confront numerous problems in extending their business and capital operations. Supply chain finance, as an innovative financial service model, opens up new funding opportunities for small and medium-sized businesses. This article first examines the fundamental concepts and operational mechanisms of supply chain finance, then investigates its current application status and problems faced by small and medium-sized enterprises, and finally proposes a path to optimize supply chain finance services for small and medium-sized enterprises using financial technology to improve their financing efficiency and overall competitiveness. Supply chain finance has sparked widespread interest among businesses, particularly small and medium-sized businesses, due to its ability to effectively integrate upstream and downstream enterprise resources, reduce financing costs, shorten financing cycles, and improve capital utilization efficiency. Small and medium-sized businesses often encounter issues such as short finance cycles and restricted credit options. Supply chain finance may link core organizations with multi-level suppliers, providing more flexible and cost-effective financing alternatives for small and medium-sized businesses.